Enhancing soil microbial diversity, quality, and crop growth through deficit irrigation combined with biochar application - Zhang, Ruxin; Qu, Zhongyi; Wang, Liping; Yang, Wei; Zhang, Dongliang; Zhao, Yibo; Li, Junjie (Frontiers in Sustainable Food Systems, 2025)
IntroductionBiochar has been widely used under irrigation conditions because of its ability to improve agricultural soil productivity and crop yield. However, the effects of deficit irrigation biochar interactions on soil quality and underlying mechanisms remain not well understood.ObjectiveThis study aimed to determine whether deficit irrigation combined with biochar could interact with soil physics, chemistry, biology, and crop growth, thereby increasing the soil quality index and affecting crop yield and quality.MethodsIn this study, we conducted a 2-year experiment with differential irrigation: full irrigation (100% ETc) and deficit irrigation (60% ETc), applying three biochar doses (B0 = 0 t ha−1, B15 = 15 t ha−1, and B30 = 30 t ha−1).ResultsThe results showed that the biochar and irrigation interaction significantly affected soil enzyme activities, nutrients, and microbial biomass carbon and adenosine triphosphate contents, resulting in an increase in the number of dominant taxa and α diversity index in the biochar treatment under deficit irrigation conditions. However, this treatment resulted in lower relative abundances of Acidobacteria, Chloroflexi, and Candidatus Rokubacteria. Biochar application improved sunflower kernel quality, aboveground biomass, and yield, with varying effects under different irrigation practices. Compared with the other treatments, the B30 treatment under deficit irrigation conditions exhibited the highest aboveground biomass and yield, with increases of 1.3–28.3% and 1.1–33.5%, respectively. However, an increase in arginine and proline contents in the seeds was only observed later in the experiment. In addition, the soil quality index was crucial for sunflower yield, with its positive effects varying based on the irrigation method used.ConclusionBiochar applied under deficit irrigation was effective in improving soil environment and soil quality in the study area, at least for the 2-year pilot study. Most importantly, biochar counteracted the adverse effects of water deficit and promoted crop seed quality and yield.SignificanceIn conclusion, deficit irrigation combined with biochar application under conditions of water scarcity may be a novel approach for improving crop yield by reducing the negative effects of drought stress.